2020
DOI: 10.1007/s00431-020-03787-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between umbilical cord blood vitamin A levels and late preterm infant morbidities: a prospective cohort study

Abstract: Background: Low plasma vitamin A levels increases the risk of neonates' morbidity. However, the relationship between umbilical cord blood (UCB) vitamin A levels and late-preterm infant (LPI) consequences is inconclusive. Herein, we attempted to clarify the association between UCB vitamin A levels and LPI morbidities. Methods: We conducted a prospective cohort study of 208 LPI (from 34+0 to 36+6 weeks gestational age) between January 1, 2014 and June 30, 2015. UCB specimens were collected shortly after birth, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…No sex differences were observed regarding the vitamin status in our study. This is in line with the findings of other studies for retinol [40,45] and α-tocopherol [53]. It is noted that male infants had a lower retinol concentration than females in another study [70]; however, after adjusting for birth weight and length, the difference was not significant [70].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No sex differences were observed regarding the vitamin status in our study. This is in line with the findings of other studies for retinol [40,45] and α-tocopherol [53]. It is noted that male infants had a lower retinol concentration than females in another study [70]; however, after adjusting for birth weight and length, the difference was not significant [70].…”
Section: Discussionsupporting
confidence: 91%
“…Although retinol cutoffs for defining a deficiency differ across studies, a retinol concentration of less than 200 µg/mL was considered as a deficiency [15] in this and other studies [11,40,44]. The retinol deficiency of infants in this study (10%) was lower than that reported by others (42-82%) [11,[45][46][47]. Moreover, SGA infants have been reported to have low levels of retinol-binding protein [48], which is well correlated to serum retinol [49].…”
Section: Discussionmentioning
confidence: 67%
“…This finding suggests that there might be a role of vitamin A in determining birth weight and underscores the importance of vitamin A nutrition in fetal growth. However, some studies have shown that maternal vitamin A concentrations were not associated with birth weight ( 10 , 25 ). The reasons behind these discrepancies might be partly due to different study participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, Enfu Tao et al. found that cord blood vitamin A concentration in late preterm infants was not associated with birth weight ( 10 ). Some meta-analysis relating to vitamin revealed that maternal vitamin D deficiency increased the risk of SGA (OR=1.588, 95% CI 1.138-2.216) ( 11 ) and LBW (OR=2.39, 95% CI 1.25-4.57) ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation